Pitting and intergranular corrosion of Scalmalloy® aluminium alloy additively manufactured by Selective Laser Melting (SLM). (June 2022) - Cabrera-Correa, Leticia; González-Rovira, Leandro; de Dios López-Castro, Juan; Botana, F. Javier
Abstract: Localized corrosion of Scalmalloy® processed by Selective Laser Melting (SLM) under certified conditions is studied and correlated with the intermetallic particles present in the microstructure. Two types of samples are considered: as-built and heat-treated samples. The heat treatment does not modify the pitting corrosion performance. All samples exhibit two groups of pits with different repassivation behaviour. Si-bearing and Fe-bearing phases produce pitting, while Al(Sc, Zr) is not found to be important. The two types of samples are resistant to intergranular corrosion (IGC) according to ASTM G67 thanks to the low content of β phase. However, the heat-treatment slightly increases the IGC-susceptibility. Highlights: Mg2 Si and Al(Fe, Mn) intermetallic phases produce pitting corrosion. There are two groups of pits according to their repassivation performance. Heat treatment at 350 ⁰C for 4 h does not alter the pitting corrosion behaviour. As-built and heat-treated alloy is IGC-resistance based on ASTM G67 classification. Heat treatment at 350 ⁰C for 4 h slightly increases the IGC-susceptibility.